Analisa Pengukuran Kualitas Website E-Recruitment PT. Angkasa Pura Suport Menggunakan Metode Webqual 4.0 - Satrio, Satrio Nugroho; Muharram, Muhammad (Software Development, Digital Business Intelligence, and Computer Engineering, 2023)
The success of developing a company's information system can be measured by the level of community satisfaction. The importance of service quality is not only based on the views of service providers, but also determined by public perceptions. To overcome the problems previously mentioned, analysis is needed to evaluate the quality of a website that is working properly or not. In order to know the quality of the website based on user opinion, the website must be tested using the Webqual 4.0 method. In this study the authors aim to analyze the quality of the e-recruitment website of PT. Angkasa Pura Support using the Webqual 4.0 method. The Webqual method has 4 variables, namely Usability (X1), Information Quality (X2), Service Interaction Quality (X3), and User Satisfaction (Y). The data collection method used is a quantitative method by distributing questionnaires to employees of PT. Angkasa Pura Support. The number of samples obtained was 60 samples from a total population of 150 people. The tests used in this research are validity test, reliability test, F test, T test, and coefficient of determination test. The results of this study indicate that each variable X1, X2, and X3 has an effect on variable Y with a significance value of 0.000 <0.005 and a calculated F value of 18.224 > 2.180 and a coefficient of determination of 49.4%.